STRATEGI PENGEMBANGAN MANAJEMEN KAMPUS DI UNIVERSITAS DARUL ULUM JOMBANG - Rubait Dasururi (Hijri, 2025)
Campus management development is an important aspect in improving the quality of service and competitiveness of higher education. This study aims to formulate an effective management development strategy at Darul Ulum University, Jombang, with a focus on system modernization, improving human resource (HR) competency, and strengthening stakeholder participation. The research method used is qualitative descriptive through interviews, observations, and documentation. The results of the study revealed that the digitalization of the academic system has been running but has not been optimally integrated, and HR competencies are not evenly distributed. Active participation of the academic community in decision making is also still limited. Therefore, the recommended strategies include the implementation of an integrated management system based on information technology, ongoing training for HR, and strengthening communication forums between stakeholders. The implementation of this strategy is expected to increase the efficiency, transparency, and accountability of campus management